Cochlear Implantation: An Overview - Deep, Nicholas L.; Dowling, Eric M.; Jethanamest, Daniel; Carlson, Matthew L. (Journal of Neurological Surgery Part B: Skull Base, 2019)
A cochlear implant (CI) is a surgically implanted device for the treatment of severe to profound sensorineural hearing loss in children and adults. It works by transducing acoustic energy into an electrical signal, which is used to stimulate surviving spiral ganglion cells of the auditory nerve. The past 2 decades have witnessed an exponential rise in the number of CI surgeries performed. Continual developments in programming strategies, device design, and minimally traumatic surgical technique have demonstrated the safety and efficacy of CI surgery. As a result, candidacy guidelines have expanded to include both pre and postlingually deaf children as young as 1 year of age, and those with greater degrees of residual hearing. A growing proportion of patients are undergoing CI for off-label or nontraditional indications including single-sided deafness, retrocochlear hearing loss, asymmetrical sensorineural hearing loss (SNHL) in adults and children with at least 1 ear that is better than performance cut-off for age, and children less than 12 months of age. Herein, we review CI design, clinical evaluation, indications, operative technique, and outcomes. We also discuss the expanding indications for CI surgery as it relates to lateral skull base pathology, comparing CI to auditory brainstem implants, and address the concerns with obtaining magnetic resonance imaging (MRI) in CI recipients.
Keywords: cochlear implantation; hearing loss; auditory prosthesis; electric stimulation; auditory nerve; auditory brainstem implant